Prevalence of a vertically transmitted single-stranded DNA virus in spinybacked orbweavers (Gasteracantha cancriformis) from Florida, USA. (18th June 2019) - Rosario, Karyna; Mettel, Kaitlin A.; Greco, Anthony M.; Breitbart, Mya
Abstract : Spiders (order Araneae, class Arachnida) are an important group of predatory arthropods in terrestrial ecosystems that have been recently identified as an untapped reservoir of single-stranded (ss)DNA viruses. Specifically, spiders harbour a diversity of ssDNA viruses encoding a replication-associated protein (Rep) within a circular genome. However, little is known about the ecology of novel circular Rep-encoding ssDNA (CRESS DNA) viruses. Here we investigated two CRESS DNA viruses recently identified in spinybacked orbweavers ( Gasteracantha cancriformis ), namely spinybacked orbweaver circular virus (SpOrbCV) 1 and 2. SpOrbCV-1 was detected in the majority (> 65 %) of spider specimens from all life stages, including eggs, spiderlings and adults, demonstrating that this virus is active within spinybacked orbweavers. In contrast, SpOrbCV-2 was only detected in adults at a lower (36 %) prevalence. Since we also detected SpOrbCV-2 in other spider species and this virus has been reported from a dragonfly, we suggest that SpOrbCV-2 is accumulated in these predators through common insect prey. The prevalence of SpOrbCV-1 in collected specimens allowed us to design assays to characterize this virus, which represents a new group of CRESS DNA viruses, the 'circularisviruses'. To our knowledge, SpOrbCV-1 is the first example of a vertically transmitted virus in spiders, which may explain its high prevalence in spinybacked orbweavers. Since vertically transmitted viruses infecting insects (class Insecta) can manipulate their host's behaviour and physiology, future studies should investigate the ecological role of vertically transmitted viruses in spiders.